Personality disorder traits, risk factors, and suicide ideation among older adults. (23rd February 2015) - Jahn, Danielle R.; Poindexter, Erin K.; Cukrowicz, Kelly C.
ABSTRACT: Background: Personality disorder traits are relatively prevalent among older adults, and can be associated with complex and chronic difficulties, including suicide risk. However, there is a lack of research regarding personality disorders and suicide ideation in older adults. Depressive symptoms and hopelessness may be important to the relation between personality disorders and suicide risk. Additionally, variables from the interpersonal theory of suicide, perceived burdensomeness and thwarted belongingness, may be critical risk factors for suicide in this population. We hypothesized that perceived burdensomeness and thwarted belongingness, theory-based variables, would act as parallel mediators of the relation between personality disorder traits and suicide ideation, whereas depressive symptoms and hopelessness would not. Methods: The hypothesis was tested in a sample of 143 older adults recruited from a primary care setting. Participants completed self-report questionnaires of personality traits, suicide ideation, depressive symptoms, hopelessness, perceived burdensomeness, and thwarted belongingness. Results: Findings from a non-parametric bootstrapping procedure indicated that perceived burdensomeness, thwarted belongingness, and depressive symptoms mediated the relation between total personality disorder traits and suicide ideation. Hopelessness did not act as a mediator. Conclusions: These findings indicate that perceived burdensomeness, thwarted belongingness, and depressive symptoms are likely important risk factors for suicide ideation among older adults. Clinicians should be aware of these issues when assessing and treating suicide risk among older adults.